2019
DOI: 10.1007/s11082-019-1992-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of first principles and semi-empirical models of the structural and electronic properties of $$\hbox {Ge}_{1-x}\hbox {Sn}_{x}$$ alloys

Abstract: We present and compare three distinct atomistic models -based on first principles and semiempirical approaches -of the structural and electronic properties of Ge1−xSnx alloys. Density functional theory calculations incorporating Heyd-Scuseria-Ernzerhof (HSE) and modified Becke-Johnson (mBJ) exchange-correlation functionals are used to perform structural relaxation and electronic structure calculations for a series of Ge1−xSnx alloy supercells. Based on HSE calculations, a semi-empirical valence force field (VF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 63 publications
8
64
0
Order By: Relevance
“…This value is consistent with the energy expected at low temperature for the optical transition through the fundamental indirect band gap of bulk Ge [30], thereby suggesting the prominence of the indirect-band-gap recombination in all the observed spectra of our coherent Ge 1−x Sn x films. The emergence of the indirect PL in Ge 1−x Sn x is also in line with the -L hybridization of the conduction-band edge pointed out by recent calculations [31,32].…”
Section: A Photoluminescence Measurementssupporting
confidence: 86%
See 1 more Smart Citation
“…This value is consistent with the energy expected at low temperature for the optical transition through the fundamental indirect band gap of bulk Ge [30], thereby suggesting the prominence of the indirect-band-gap recombination in all the observed spectra of our coherent Ge 1−x Sn x films. The emergence of the indirect PL in Ge 1−x Sn x is also in line with the -L hybridization of the conduction-band edge pointed out by recent calculations [31,32].…”
Section: A Photoluminescence Measurementssupporting
confidence: 86%
“…The measured carrier lifetime τ corresponds to an effective lifetime for photogenerated carriers and encapsulates contributions from radiative (τ R ) and nonradiative (τ NR ) recombination processes: τ −1 = τ −1 R + τ −1 NR [44]. Recent analyses [31,32,45] have shown that the evolution of the Ge 1−x Sn x band gap is driven by Sn-induced hybridization between the Ge -point and L-point conduction-band-edge states. A direct band gap then emerges continuously with increasing Sn content, as the alloy conduction-band edge acquires increasing direct ( ) character.…”
Section: B Hanle Measurements and Carrier Lifetimementioning
confidence: 99%
“…4(a) we compare the calculated Raman spectra of ordered and disordered supercells having the same Sn composition, x = 6.25%: an ordered 16-atom Ge 15 Sn 1 supercell (upper panel), and configuration averaging over 25 distinct, disordered 512-atom Ge 480 Sn 32 supercells (lower panel). Figure 4(b) shows the distribution of relaxed nearest-neighbour bond lengths in these supercells, sorted into bins of width 0.01 Å, 46,72 where the distribution for the disordered Ge 480 Sn 32 supercells has again been obtained via configurational averaging. Note that in Fig.…”
Section: B Impact Of Alloy Disordermentioning
confidence: 99%
“… 7 11 Recent theoretical calculations have also supported that the indirect-gap to direct-gap transition proceeds via the continuous transition–with increasing x . 11 , 12 The optical and optoelectronic properties of an alloy can be influenced by the alloy composition, as demonstrated both theoretically 13 and experimentally. 14 16 A definitive transition to a direct bandgap is required, with large enough Sn incorporation, for the use of Ge 1– x Sn x in efficient optoelectronic devices, such as photodiodes and photodetectors and photonic devices without the need for any external force such as induced strain.…”
Section: Introductionmentioning
confidence: 96%